Rebels and traitors - Davis, Lindsey, 1949- (Arrow Books, 2009)
Set against the terrible struggle of the English Civil War and the dark plots of the Commonwealth, Rebels and Traitors tells of soldiers, adventurers, aristocrats and kings, tradesmen, politicians, radicals and scavengers - and the hopes and dreams that carried them through one of the most turbulent eras of English history. Men who never imagined fighting a war gladly risk their lives; women strive to keep families and businesses together through years of deprivation; innocents are caught up in bloodshed and terror.